Enhanced electrochemical performance of MnO2/NiO nanocomposite for supercapacitor electrode with excellent cycling stability - Racik, K. Mohamed; Guruprasad, K.; Mahendiran, M.; Madhavan, J.; Maiyalagan, T.; Raj, M. Victor Antony (Journal of materials science. Materials in electronics, 2019)
Transition metal oxides with metallic composites have greater attention for hybrid supercapacitor due to their excellent electrochemical performance and low cost. In this study, the preparation of manganese dioxide/nickel oxide (MnO 2 /NiO) nanocomposite via a facile hydrothermal method is reported. The crystallographic and morphological features were studied by Powder XRD, FTIR, HRSEM, EDX and TEM analysis. Cyclic voltammetry, galvanostatic charge–discharge and impedance analysis are implemented in order to examine the applicability of the MnO 2 /NiO nanocomposite electrode material as a supercapacitor. The MnO 2 /NiO composites revealed good electrochemical performance by exhibiting a specific capacitance of 247 Fg −1 at the discharge current density rate of 0.5 Ag −1 using 1 M KOH as the electrolyte. Moreover, the composite electrode shows enhanced cycling stability. The improvement in specific capacitance of the MnO 2 /NiO composite is primarily due to its hybrid structure, which offers a better contact of surface of electrode and electrolyte, and active sites with large scale. These results expose the development of MnO 2 /NiO electrode material shown enhanced performance for supercapacitors.